Stochastic Diffusion Analysis for Sustainable Green Innovation - Yenming J. Chen (International Journal of Automation and Smart Technology, 2013)
This study investigates the sustainability of green innovation under the influence of coopetitive diffusion. We focus on green innovations which repurpose discarded technology accessories for resale. Original manufacturers make every attempt to prevent the use of low-cost replacements. To encourage green innovation, incumbent market leaders need to be provided with business strategies which help them maximize profitability. Using a stochastic differential game from a Lotka–Volterra system, we predict a coopetitive diffusion path among participant stakeholders. We find that green innovation, combined with the positive effect of network externalities can indeed enhance total market growth. Factors such as product characteristics, product pricing, and compatibility protection strategies must interact properly for green innovation to be sustainable.